Drought Frequency at Hagari and Bijapur - Ratnam, B P; Joshi, S N (Annals of Arid Zone, 2016)
The occurrence of drought during the monsoon in two typical arid stations of Karnataka State was studied. Hagari experienced 10 drought spells and Bijapur 9 during a study covering a period of 20 years (1954-1973). The elements of water balance for the normal as well as for the disastrous drought years have been discussed. Maldistribution and low amounts of rainfall have been considered to have the four disastrous droughts.